A Systematic Review of Creativity-Related Studies Applying the Remote Associates Test From 2000 to 2019 - Wu, Ching-Lin; Huang, Shih-Yuan; Chen, Pei-Zhen; Chen, Hsueh-Chih (Frontiers in Psychology, 2020)
The study examines how the remote associates test (RAT) has been used to examine theories of creativity through a review of recent studies on creativity. Creativity-related studies published between 2000 and 2019 were retrieved from the SCOPUS database. A total of 172 papers were chosen for further analysis. Content analysis shows that research on creativity using RAT mainly concerns remote association, insight problem-solving, general creative process, test development, individual difference, effect of treatment, clinical case, social interaction effect, and predictor or criterion. The study constructs a theoretical framework based on the 4P (Product-Person-Process-Place) model, and demonstrates how empirical studies using the RAT explore the individual differences, internal processes, and external influences of creative thinking. In addition, the most commonly used versions of the RAT is the Compound Remote Associates Problems (Bowden & Jung-Beeman, 2003a). Current research shows a trend whereby the creative thinking process has been receiving greater attention. In particular, a growing number of studies in this field have been carried out using cognitive neuroscience technologies. These findings suggest that the RAT provides researchers with a way to deepen their understanding of different levels of creativity.